Pengaruh Komposisi Pupuk NPK terhadap Pertumbuhan Fase Generatif Labu Madu Asal Perbanyakan Vegetatif - Ruroh, Siti Masruroh; ., Mawadi (Program Studi Agroteknologi, 2022)
Honey gourd is one of the short-lived plant commodities thathasthe potential to withstand land conversion. The use of seed origin from vegetative propagation of honey gourd can help farmers obtain pumpkin seeds easily and at affordable price. Giving the right composition of NPK fertilizer ratio will help the honey pumpkin plant growth process properly. This study used a randomized block design (RAK) with a factorial pattern, the first factor being 3 treatment from seed (B) and the second factor 3 treatments from fertilizer composition (K), repeated 3 times. So the total experiment was 27 plants. The treatments used were B1 from the seeds of the 3rd segment, B2 from the seeds of the 4th segment, B3 from the seeds of the 5th segment, K1 from the composition of NPK 1:1:1, K2 from the composition of NPK 1:2:2, K3 composition of NPK 1:2:3. The test iscarried out by F-test with analysis of variance (ANOVA), if there is a significant difference (F-count > F-table) the proceed with the DMRT 5%/2.